INVESTIGATION OF LOCALIZED ELECTROMAGNETIC FIELD IN A SUBWAVELENGTH METALLIC SLIT - Arakelyan, Sh.Kh. (Proceedings of the YSU A: Physical and Mathematical Sciences, 2017)
Electromagnetic field localization in a subwavelength metallic slit by a thermo-elastic optical indicator microscope (TEOIM) was investigated. As an indicator for the TEOIM system a slide glass with sizes of $20× 20×0.5~(mm)$ was used, on the surface of which an $Al$ film of $20~nm$ thickness was vaporized using the vacuum evaporation technique, with various slit width $(10-50~μ m).$ Strongly localized electromagnetic field has been exited in the slits by $50~ GHz$ generator and was visualized by a TEOIM. The waveguide properties of the system were characterized by COMSOL Multiphysics$^{\circledR}$ additionally. The simulation results are in good agreement with the visualization data set.
Keywords: subwavelength metallic slit; thermo-elasticity; visualization; field localization